Chronic White Matter Inflammation and Serum Neurofilament Levels in Multiple Sclerosis. (10th August 2021) - Maggi, Pietro; Kuhle, Jens; Schädelin, Sabine; van der Meer, Franziska; Weigel, Matthias; Galbusera, Riccardo; Mathias, Amandine; Lu, Po-Jui; Rahmanzadeh, Reza; Benkert, Pascal; La Rosa, Francesco; Bach Cuadra, Meritxell; et al.
Abstract : Objective: To assess whether chronic white matter inflammation in patients with multiple sclerosis (MS) as detected in vivo by paramagnetic rim MRI lesions (PRLs) is associated with higher serum neurofilament light chain (sNfL) levels, a marker of neuroaxonal damage. Methods: In 118 patients with MS with no gadolinium-enhancing lesions or recent relapses, we analyzed 3D-submillimeter phase MRI and sNfL levels. Histopathologic evaluation was performed in 25 MS lesions from 20 additional autopsy MS cases. Results: In univariable analyses, participants with ≥2 PRLs (n = 43) compared to those with ⩽1 PRL (n = 75) had higher age-adjusted sNfL percentiles (median, 91 and 68; p < 0.001) and higher Multiple Sclerosis Severity Scale scores (MSSS median, 4.3 and 2.4; p = 0.003). In multivariable analyses, sNfL percentile levels were higher in PRLs ≥2 cases (βadd, 16.3; 95% confidence interval [CI], 4.6–28.0; p < 0.01), whereas disease-modifying treatment (DMT), Expanded Disability Status Scale (EDSS) score, and T2 lesion load did not affect sNfL. In a similar model, sNfL percentile levels were highest in cases with ≥4 PRLs (n = 30; βadd, 30.4; 95% CI, 15.6–45.2; p < 0.01). Subsequent multivariable analysis revealed that PRLs ≥2 cases also had higher MSSS (βadd, 1.1; 95% CI, 0.3–1.9; p < 0.01), whereas MSSS was not affected by DMT or T2 lesion load. On histopathology, both chronic active and smoldering lesions exhibited more severe acute axonal damage at the lesion edge than in the lesion center (edge vs center: p = 0.004 and p = 0.0002, respectively). Conclusion: Chronic white matter inflammation was associated with increased levels of sNfL and disease severity in nonacute MS, suggesting that PRL contribute to clinically relevant, inflammation-driven neurodegeneration.